Habitat suitability of Anopheles vector species and association with human malaria in the Atlantic Forest in south-eastern brazil - Laporta, Gabriel Zorello; Ramos, Daniel Garkauskas; Ribeiro, Milton Cezar [UNESP]; Mureb Sallum, Maria Anice (Fundacão Oswaldo Cruz, 2011)
Every year, autochthonous cases of Plasmodium vivax malaria occur in low-endemicity areas of Vale do Ribeira in the south-eastern part of the Atlantic Forest, state of São Paulo, where Anopheles cruzii and Anopheles bellator are considered the primary vectors. However, other species in the subgenus Nyssorhynchus of Anopheles (e. g., Anopheles marajoara) are abundant and may participate in the dynamics of malarial transmission in that region. The objectives of the present study were to assess the spatial distribution of An. cruzii, An. bellator and An. marajoara and to associate the presence of these species with malaria cases in the municipalities of the Vale do Ribeira. Potential habitat suitability modelling was applied to determine both the spatial distribution of An. cruzii, An. bellator and An. marajoara and to establish the density of each species. Poisson regression was utilized to associate malaria cases with estimated vector densities. As a result, An. cruzii was correlated with the forested slopes of the Serra do Mar, An. bellator with the coastal plain and An. marajoara with the deforested areas. Moreover, both An. marajoara and An. cruzii were positively associated with malaria cases. Considering that An. marajoara was demonstrated to be a primary vector of human Plasmodium in the rural areas of the state of Amapa, more attention should be given to the species in the deforested areas of the Atlantic Forest, where it might be a secondary vector.
Keywords: Atlantic Forest; disease vectors; spatial distribution; vivax malaria